Sudden Cardiac Death in Children. Part 1 - Ye.V. Pshenichnaya (Zaslavsky O.Yu., 2013)
This article presents the prevalence, terminology, classification of sudden cardiac death. A description of congenital structural heart diseases associated with a risk of sudden cardiac death is given. The issues of etiology and pathogenesis of life-threatening conditions are described in detail.